Employee turnover intention among Millennials: The role of psychological well-being and experienced workplace incivility - Reny Yuniasanti; Nurul Ain Hidayah binti Abas; Hazalizah Hamzah (HUMANITAS: Indonesian Psychological Journal, 2019)
High turnover intention is a problem in the workforce today. The purpose of this study is to determine the relationship between experienced workplace incivility and psychological well-being on turnover intention. The subjects of this study were 46 millennial employees who had worked for at least three months. Data were collected with turnover intention scale, experienced workplace incivility scale, and psychological well-being scale. Partial Least Square PLS-SEM analysis was used to analyze the data. Findings indicate that experienced workplace incivility is positively related to turnover intention, while psychological well-being is negatively related to employee turnover intention. The results show that workplace incivility affects employee turnover intention higher than psychological well-being for millennial employees. Connections and communality are characteristics of millennial employees; therefore, they consider that the environment is essential. It is essential for employers to develop a work condition that minimalizes experienced workplace incivility and improves the psychological well-being of their employees to reduce turnover intention among millennial employees.